Diagnosis of Superior Semicircular Canal Dehiscence in the Presence of Concomitant Otosclerosis. Issue 8 (September 2017) - Yong, Michael; Zaia, Erica; Westerberg, Brian; Lea, Jane
Abstract : Objective: To review three patients with concurrent otosclerosis and superior canal dehiscence identified before operative intervention and provide a practical diagnostic approach to this clinical scenario. Study Design: Retrospective patient series. Setting: Tertiary/quaternary referral center. Patients: Individuals with confirmed diagnoses of concurrent otosclerosis and superior semicircular canal dehiscence syndrome. Interventions: Detailed history and physical examinations were performed on these patients, as well as detailed audiovestibular testing and computed tomography imaging. Main Outcome Measures: Establishing a clear diagnosis of concurrent otosclerosis and superior semicircular canal dehiscence syndrome using a thorough diagnostic approach. Results: Three patients presented with conductive hearing loss and normal tympanic membranes. When history and physical examination yielded suspicious third window symptoms/signs, more detailed audiovestibular testing and computed tomography scan imaging were performed. All three patients were ultimately identified to have concurrent otosclerosis and superior canal dehiscence. Conservative management was the option of choice for two of these patients (trial of a hearing aid) and surgical intervention was performed to treat the otosclerosis in the remaining patient.